2005
DOI: 10.1590/s1517-83822005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus antibodies in swine herds of Mato Grosso state, Central Brazil

Abstract: There is no information about evidence of hepatitis E virus (HEV) infection in swines in Central Brazil. In order to assess if HEV circulates in swines of the State of Mato Grosso, Central Brazil, a seroprevalence study was conducted including pigs from 17 farms, corresponding to 13 counties. The animals were randomly chosen among pigs arriving to two slaughterhouses between December 2002 and February 2003. Serum samples were collected and tested for IgG antibodies against HEV (anti-HEV) by enzyme immunoassay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…We found that among pigs from this region 9.9% (15/151) were currently infected with HEV (HEV RNA positive); these findings confirm the circulation of HEV among pigs in Brazil, where pigs with HEV infection also has been reported in other three different regions of the country [14,15,27]. The prevalence of anti-HEV IgG found among pigs from Pará state was lower (8.6%; 13/151) than that previously reported among pigs from other Brazilian regions: in pigs from Mato Grosso state a high (81.2%) seroprevalence of anti-HEV IgG was found [28], whereas in the Rio de Janeiro state, at southeastern region, the seroprevalence was 24.3% [29]. Differences in prevalence of serological markers of HEV infection (anti-HEV IgG/IgM) around the world have been related to specificity and sensibility of the commercially available serological assays and this may explain the differences seen in HEV seroprevalence results among pigs from different regions of Brazil [30].…”
Section: Discussionsupporting
confidence: 89%
“…We found that among pigs from this region 9.9% (15/151) were currently infected with HEV (HEV RNA positive); these findings confirm the circulation of HEV among pigs in Brazil, where pigs with HEV infection also has been reported in other three different regions of the country [14,15,27]. The prevalence of anti-HEV IgG found among pigs from Pará state was lower (8.6%; 13/151) than that previously reported among pigs from other Brazilian regions: in pigs from Mato Grosso state a high (81.2%) seroprevalence of anti-HEV IgG was found [28], whereas in the Rio de Janeiro state, at southeastern region, the seroprevalence was 24.3% [29]. Differences in prevalence of serological markers of HEV infection (anti-HEV IgG/IgM) around the world have been related to specificity and sensibility of the commercially available serological assays and this may explain the differences seen in HEV seroprevalence results among pigs from different regions of Brazil [30].…”
Section: Discussionsupporting
confidence: 89%
“…There was no difference in prevalence between genders (p=0.1) and age classes (p=0.58), once again concurring with Guimarães et al (2005). This can be explained because both studies analyzed only young and adult samples and the disease appears to have no preference among genders.…”
Section: Discussionsupporting
confidence: 57%
“…A high prevalence of anti-HEV IgG was detected in domestic pigs in the Federal District. A high prevalence of swine anti-HEV antibodies was also detected by Guimarães et al (2005) (Souza et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the state of Mato Grosso (MT), which is one of the top regions for swine production in Brazil, there is evidence for a high level of circulation of genotype 3 HEV among swine (Guimarães et al 2005, dos Santos et al 2009). However, it has not been investigated whether individuals who came into contact with these animals would possess an increased risk for this type of infection.…”
mentioning
confidence: 99%